Enhanced Transmit Antenna Selection Scheme for Secure Throughput Maximization Without CSI at the Transmitter - Alves, Hirley; De Castro Tome, Mauricio; Nardelli, Pedro Henrique Juliano; De Lima, Carlos H. M. [UNESP]; Latva-Aho, Matti (Institute of Electrical and Electronics Engineers (IEEE), 2016)
This paper addresses the establishment of secure communication links between Alice and Bob in the presence of an eavesdropper (Eve). The proposed scenario assumes: 1) MIMOME wiretap channel; 2) transmit antenna selection at the Alice; 3) no channel state information at the transmitter; 4) fixed Wyner codes; and 5) guarantee of secure throughput by both quality of service and secrecy outage constraints. We propose a simple protocol to enhance security via transmit antenna selection, and then assess its performance in a closed form by means of secrecy outage and successful transmission probabilities. We assume these probabilities are our constraints and then maximize the secure throughput, establishing a security-reliability tradeoff for the proposed scenario. Our numerical results illustrate the effect of this tradeoff on the secure throughput as well as on the number of antennas at Alice, Bob, and Eve. Interestingly, a small sacrifice in reliability allows secrecy enhancement in terms of secure bps/Hz. We apply this idea in our smart grid application (where Alice represents a smart meter and Bob an aggregator) to exemplify that, although Eve may acquire some samples of the average power demand of a household, it is not enough to properly reconstruct such curve.
Keywords: Physical layer security; secrecy outage probability; secure throughput; smart-grids